Ultrasound-aided In Situ Transesterification of oil Adsorbed on Decanter Cake Using Efba and Na2SiO3 as Catalysts - Gaanty Pragas, Maniam; Noor, Hindryawati; Irma, Nurfitri; Rajan, Jose; M. H. A., Rahim; M. M., Yusoff (2014)
In the present study, renewable green fuel is produced using abundant biowaste from palm oil mill. The crude plam oil from decanter cake was transesterify using empty fruit bunch ash (EFBA) and waste marine sponge with sodium (Na2SiO3-WMS) under very mild conditions. The EFBA as a solid catalyst was calcined at 500 ˚C for 5 h, while Na2SiO3-WMS was prepared using impregnation method, then calcined at 500 ˚C for 3 h. Parametric study has been conducted and the optimal conditions were found to be: MeOH:oil mass ratio of 6:1 and 2.3 wt.% catalyst (based on DC weight) at 55 °C, yielding highest methyl ester conversion of 85.9 (under EFBA) and 90% (under Na2SiO3) within 1 h reaction time. Ultrasound undoubtedly assisted in transesterification achieving this remarkable result than mechanical stirring